Pengaruh Brand Awareness, Brand Image dan Brand Loyalty Terhadap Brand Equity Pada Pengguna Produk Nike di Kabupaten Tangerang - Rudi Yacub (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The sports industry has a very large potential income and is followed by the enthusiasm of the community to exercise, which is an opportunity for entrepreneurs in the sports equipment industry. The objectives of this study are: First, to explore the effects of brand awareness on brand equity. Second, to explore the effect of brand image on brand equity. Third, explore brand loyalty to brand equity. The data collection method is convenience sampling. The research sample was collected from 160 respondents, who use Nike products in Tangerang Regency. The data analysis technique used in this study is multiple regression analysis through the Statistical Package for the Social Science computer program version 18. The results are: (1) brand awareness has a positive impact on brand equity; (2) brand image has a positive impact on brand equity; (3) Brand loyalty is the main impact on brand equity Keywords : Brand Awarness, Brand Image, Brand Loyalty, Brand Equity